2017
DOI: 10.1111/jfd.12598
|View full text |Cite|
|
Sign up to set email alerts
|

Virulence and genotypes of white spot syndrome virus infecting Pacific white shrimp Litopenaeus vannamei in north‐western Mexico

Abstract: White spot syndrome virus (WSSV) has caused substantial global economic impact on aquaculture, and it has been determined that strains can vary in virulence. In this study, the effect of viral load was evaluated by infecting Litopenaeus vannamei with 10-fold serial dilution of tissue infected with strain WSSV Mx-H, and the virulence of four WSSV strains from north-western Mexico was assessed along with their variable number of tandem repeat (VNTR) genotypes in ORF75, ORF94 and ORF125. The LD of the Mx-H strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
9
0
3
Order By: Relevance
“…AF332093), and South Korea (GenBank no. JX515788)] have been sequenced, but they are all classified as a single species of the genus Whispovirus (family Nimaviridae) [ 24 , 28 ]. The complete genome sequence of WSSV isolates was reported in 2001 (WSSV-TH, GenBank no.…”
Section: Dna Viral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…AF332093), and South Korea (GenBank no. JX515788)] have been sequenced, but they are all classified as a single species of the genus Whispovirus (family Nimaviridae) [ 24 , 28 ]. The complete genome sequence of WSSV isolates was reported in 2001 (WSSV-TH, GenBank no.…”
Section: Dna Viral Diseasesmentioning
confidence: 99%
“…EF468499). The low-virulence strain Mx-G has additional repeat units (RUs) in ORF94 when compared to the highly virulent strain Mx-H, and both have 100% identity in the variable number of tandem repeats (VNTR) in ORF75 and ORF125 [ 28 ]. During the spread of WSSV in Asia, significant changes were observed in the ORF14/15 and ORF23/24 regions, and consequently, WSSV strains increased host mortality, shortened host survival, and developed increased competencies in host competition [ 43 ].…”
Section: Dna Viral Diseasesmentioning
confidence: 99%
“…Based on genomic mapping conducted by Marks et al (2004) on WSSV strains collected La identificación de las regiones variables del ADN, han permitido tipificar al genoma del VSMB en diferentes países de América (Muller et al, 2010;Ramos-Paredes et al, 2017;Pereira et al, 2019;Rodrigues et al, 2020), África (Tang et al, 2013;Onihary et al, 2021) y Asia (Dieu et al, 2004;Pradeep et al, 2008;Li et al, 2016;Min et al, 2023). Además, ha permitido reconstruir las rutas epidemiológicas que ha seguido el VSMB durante su dispersión a través del mundo (Zeng, 2021), así como también evaluar los cambios que se pueden presentar en su virulencia (Marks et al, 2005;Li et al, 2016;Ramos-Paredes et al, 2017;Min et al, 2023).…”
Section: Introductionunclassified
“…Identification of variable DNA regions has facilitated WSSV genome typing across the Americas (Muller et al, 2010;Ramos-Paredes et al, 2017;Pereira et al, 2019;Rodrigues et al, 2020), África (Tang et al, 2013;Onihary et al, 2021), and Asia (Dieu et al, 2004;Pradeep et al, 2008;Li et al, 2016;Min et al, 2023). This information has enabled the reconstruction of the epidemiological routes taken by WSSV during its global dissemination (Zeng, 2021), and the assessment of potential changes in virulence (Marks et al, 2005;Li et al, 2016;Ramos-Paredes et al, 2017;Min et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This can be examined by analyzing the natural history of disease, which is typically conducted through longitudinal studies that follow a group of infected individuals over time and monitor health outcomes [ 19 , 20 ]. Though many studies have been reported on infectivity [ 21 , 22 , 23 , 24 ], pathogenicity [ 5 , 25 , 26 , 27 , 28 , 29 ], and virulence of different WSSV strains [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], these concepts do not fully describe the progress of a disease process in an individual host over time from the asymptomatic stage to its cessation as recovery, disability, or death [ 19 , 37 ]. A natural history of disease study as such has not been reported for WSD in L. vannamei ; this is unfortunate, because the data from such a study could be used to analyze the disease pattern and ultimately characterize the epidemic pattern of spread [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%